Optimization of Kamsel Units through Police Goes to School in Preventing Traffic Accidents in the Jurisdiction of Polres Brebes - Zuhri, Rizki Syaifudin (Advances in Police Science Research Journal, 2024)
The number of traffic accidents is high and has not decreased every year in the Brebes Police area. This phenomenon is closely related to the task of the Kamsel unit in providing community and student education in the Brebes Police area. This study aims to describe the management process and organizational resources of the Kamsel unit in carrying out police going to school activities and to find out the factors that influence the process of optimizing the Kamsel unit through the police going to school. This study uses a qualitative approach with data collection methods through interviews with the Head of Police, Head of Traffic Unit, Head of South Kalimantan Unit and students; direct observation for 2 (two) weeks in the field; and documentation study. Data obtained from primary and secondary data sources. The author uses data triangulation to obtain data validity. While type of this research is field research which aims to obtain data directly through observation. Theories and concepts used in this study include management theory which is used to analyze the problem, there are the management theory carried out by the Kamsel unit, that theory is used in analyzing the problem of resources owned by the Kamsel unit. The concept of community education, the concept of the police going to school, and the concept of traffic accidents are used to describe and explain matters related to research. It was concluded that it is necessary to optimize school police activities. This can be achieved by fulfilling the management process and management elements owned by the Kamsel unit. If the implementation of activities runs optimally, the purpose of preventing traffic accidents can be carried out properly to this research objectives.